Assessing student confidence, competence and calibration: a simulation approach to discussing readiness for forensic practice. - Lattas, Dimitra; Jefferies, Gerard; Davis, Cindy; Creamer, Catherine (Social Work Education, 2026)
Case management in the criminal justice system includes conducting psychosocial assessments, identifying risks, developing intervention strategies, navigating services, monitoring/evaluation, and advocacy. Social work and criminology graduates are equally qualified for forensic case management positions, yet the work readiness of these graduates is poorly understood. This study used a simulated client interview in a community corrections context to explore students' confidence, performance, and the calibration between these. The study used a quantitative, non-randomized pre-experimental design with a pre-and-post online survey via Qualtrics. Participants included a total of 106 social work and criminology students in Australia aged 20–73 years. The results did not find a correlation between confidence and performance, raising questions about how self-efficacy transfers and functions across social work tasks and contexts. Students' self-reported confidence often did not reflect the assessed performance during the simulation. This was most evident around the skill of engaging in trauma-informed practice and managing ethical dilemmas. The findings highlight difficulties in operationalizing theoretical knowledge into discernible skills for forensic practice. It is recommended that a greater focus be given to adaptive learning to assist graduates with building confidence and skills to support clients within the criminal justice system.